Changing economic systems and institutional dimensions of the Triple Helix model - Farshad Momeni; Ali Arab Mazar Yazdi; Seyed Mohammad Sajjad Najafi (Journal of Innovation and Entrepreneurship, 2019)
In recent decades, many efforts have been put into understanding and determining key variables and factors affecting knowledge-based economy. Triple Helix model is a model with relative success in this regard; however, there is still a long way to go until it can provide policy makers and researchers with an inclusive and deep insight. Researchers of the current study strived to distinguish one of the main theoretical shortcomings of the model, i.e., considering reward systems reformation firmly fixed in the institutional framework of society, while introducing an overview of the Triple Helix model and its underlying logic using a descriptive-analytical method based upon theoretical framework of new institutionalism. This paper aims to highlight that, in the developing countries' path toward a knowledge-based economy, reward systems reformation plays a key role and it is worth to be considered in models of determining the knowledge-based economy, the Triple Helix model, in particular.
Keywords: O10; O43; B52; 650; Innovation; Knowledge-based economy; Triple Helix model; Reward system